Pengaruh Aflatoksin 9,58 ppb dalam Pakan Terhadap Biometrik Saluran Cerna dan Berat Badan Ayam Petelur Periode Awal Pertumbuhan - Pratama, Dio Putra; Tehupuring, Benjamin Chr.; Poetranto, Emmanuel Djoko; Eliyani, Hana; Soeharsono, Soeharsono; Tyasningsih, Wiwiek; Hendarti, Gracia Angelina (Universitas Airlangga, 2020)
The purpose of this study was to determine the effect of aflatoxin content of 9.58 ppb in feed on gastrointestinal biometrics and weight gain of laying hens in the early growth period. Thirty-six day old chicks (DOC) were used in this study and were divided into two groups P0 and P1. P0 (control group) was fed with 100% basal diet and P1 (treatment group) was fed a diet with a composition of 80% basal feed + 20% aflatoxin-containing feed. After the DOC was adapted, the first feeding containing aflatoxin was given from the 20th day to the 60th day. Data collection was carried out three times, namely the 20th, 40th, and 60th days. At the end of each period, the chickens would be euthanized to collect data on the weight and length of the digestive tract and body weight. Weight gain with time increased, but had no significant effect (p>0.05) between the control and treatment groups. Body weight continues to increase because the body's homeresis function is still running well. Observations on gastrointestinal biometrics showed significant differences (p<0.05) in oesophagus weight, proventriculus weight, ventriculus weight, jejunum weight, ileum weight and length, and cecum weight because aflatoxins have a direct effect on the digestive tract they pass. The conclusion of this study was that the provision of 20% aflatoxin-containing feed did not affect weight gain but had shown an effect on the biometrics of several gastrointestinal tracts.